PERBANDINGAN KADAR LEMAK DAN BERAT JENIS SUSU SAPI PERAH Friesian Holstein (FH) DI BENDUL MERISI, SURABAYA (Dataran Rendah) dan NONGKOJAJAR, PASURUAN (Dataran Tinggi) - Ruswandono Wirjatmadja; Olan Rahayu Puji Astuti Mussa; Ratna Widyawati; M Dzaki Wiranda Pratama (VITEK : Bidang Kedokteran Hewan, 2020)
This study aims to compare the quality of Friesian Holstein (FH) dairy cows in Bendul Merisi, Surabaya (Lowlands) and Nongkojajar, Pasuruan (Highlands), with the physical quality standard of fresh milk which is the national reference or SNI. This study used 60 samples of cow's milk, 30 samples from Bendul Merisi, and 30 samples from Nongkojajar. The sample was tested in the laboratory using the fat content and specific gravity test, the data obtained were calculated using the T-test formula. The data obtained from the average fat content test in Nongkojajar was 3.3685%, and the average fat content in Bendul Meisi was 4.8003%. The average density at Nongkojajar is 1.024767 mg / dl, the average density at Bendul Merisi is 1.28067 mg / dl. Based on the results of statistical calculations resulted in a significant difference (P <0.01) in the fat content test, statistical calculations resulted in a significant difference (P <0.01) in the specific gravity test.